A Pragmatic Analysis of Persuasive Language in Sunscreen Advertisements and Its Influence on Students’ Buying Decisions - Dian Saputri; Ria Rahmawati; Tatu Siti Rohbiah (Universitas Muhammadiyah Palu, 2026)
The impact of persuasive language in sunscreen ads on students' purchasing choices is the subject of this research. The purpose of the study is to determine the different types of conversational implicatures and persuasive techniques used in sunscreen commercials disseminated via social media networks like Instagram, TikTok, and YouTube. Particularly for college students, who are regularly subjected to online advertisements, social media has become a powerful marketing channel in the digital age. Sunscreen advertisements frequently use engaging images and persuasive language to influence consumers' attitudes, feelings, and purchasing decisions. As a result, this research investigates how language is intentionally employed to sway readers while also presenting facts about sunscreen products. This study uses a descriptive qualitative approach to examine students' reactions to advertisements by analyzing slogans, headlines, taglines, promotional claims, and product descriptions. College students who actively use social media and are regularly exposed to online sunscreen ads were interviewed and observed in semi structured data collecting sessions. The study is based on Grice's Conversational Implicature theory and Petty and Cacioppo's Elaboration Likelihood Model (ELM). The research shows that sunscreen ads often employ conversational implicatures both generalized and specific to indirectly sway consumers and foster favorable attitudes about the product. Through their exaggerated claims, scientific language, emotional appeals, and restricted product information, the advertisements also break Grice's maxims, especially the maxim of quantity. In addition, university students in today's digital advertising environment are influenced by persuasive methods in both central and peripheral ways, which have an impact on their attitudes, opinions, and willingness to buy sunscreen products.